2021
DOI: 10.1002/chem.202005086
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Synthetic Oligoarylamides: Privileged Structures for Medical Applications

Abstract: The term “privileged structure” refers to a single molecular substructure or scaffold that can serve as a starting point for high‐affinity ligands for more than one receptor type. In this report, a hitherto overlooked group of privileged substructures is addressed, namely aromatic oligoamides, for which there are natural models in the form of cystobactamids, albicidin, distamycin A, netropsin, and others. The aromatic and heteroaromatic core, together with a flexible selection of substituents, form conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 146 publications
(162 reference statements)
0
11
0
1
Order By: Relevance
“…Außerdem verleiht sie dem Peptid Resistenz gegen proteolytischen Abbau [12] . Darüber hinaus haben AOF s selbst das Potenzial, direkt mit Proteinen zu interagieren, [13] und sie existieren als Naturprodukte [14] . Es war daher ein logischer nächster Schritt, die ribosomale Translation nicht nur mit der Herstellung eines AOF ‐Peptid‐Makrozyklus, sondern mit einer ganzen DNA‐kodierten Bibliothek solcher Makrozyklen zu erproben.…”
Section: Figureunclassified
“…Außerdem verleiht sie dem Peptid Resistenz gegen proteolytischen Abbau [12] . Darüber hinaus haben AOF s selbst das Potenzial, direkt mit Proteinen zu interagieren, [13] und sie existieren als Naturprodukte [14] . Es war daher ein logischer nächster Schritt, die ribosomale Translation nicht nur mit der Herstellung eines AOF ‐Peptid‐Makrozyklus, sondern mit einer ganzen DNA‐kodierten Bibliothek solcher Makrozyklen zu erproben.…”
Section: Figureunclassified
“…As the D-E-F fragment of the C-terminal part of albicidin shares its main structural features with aromatic oligoamides (AOA), 42 it is to be expected that albicidin might show coordination patterns similar with AOA and its geometrical structure can be analysed in in the same way. It has been shown that the incorporation of hydrogen acceptors, such as alkoxy substituents or a heterocyclic nitrogen into the aromatic rings of the AOA scaffold results in the formation of intramolecular hydrogen bonds (IMHB), which are responsible for conformational restrictions leading to a number of molecular architectures.…”
Section: Computational Analysismentioning
confidence: 99%
“…Pyrrolamides are characterized by the presence of 4-aminopyrrole-2-carboxylate groups linked by amide bonds. They exhibit a large range of biological activities (antiviral, antimicrobial or anthelmintic activities), mainly due to their ability to bind into the minor groove of the DNA (10). Indeed, congocidine and distamycin have been extensively studied for the specificity of their binding to DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Physical studies (e. g. X-ray structure determination and circular dichroism measurements) have shown that they exhibit a marked preference for A/T rich DNA regions (11,12). Many analogs and hybrids of congocidine and distamycin have been synthesized chemically, in attempts to modify or increase the sequence specificity of the DNA binding for gene expression regulation applications (10), or to create new nontoxic antimicrobial molecules (13).…”
Section: Introductionmentioning
confidence: 99%